Access to finance, technology investments and exporting decisions of Indian services firms - Yang, Shubin; Milner, Chris; Lancheros, Sandra; Gunessee, Saileshsingh (Springer, 2020)
This study provides fresh empirical evidence on the influence of various financing sources on firms’ technology investments and exporting decisions using a panel of firms from the service sector in India during the period 1999–2010. Allowing both activities to be jointly determined, our results show that the source of finance matters for exporting and investing in technology. Moreover, the importance of different types of finance varies across industries in the service sector. Overall, we find that internal funds and non-conventional sources of finance play an important role for exporting and investing in technology in both modern and traditional services. However, funding from conventional financial markets exerts divergent effects across service industries: while traditional service firms use resources from the banking sector to fund their technological investments, firms in the modern service sector rely more on funds raised through equity markets to support their exporting and technological efforts. These results contribute to the academic literature and policy debate on the importance of financial mechanisms to promote firms’ strategic investment decisions.